Distinct roles of putrescine and spermidine in the regulation of ornithine decarboxylase in Neurospora crassa. - Davis, R H (1985)
We wished to identify metabolic signals governing changes in ornithine decarboxylase (L-ornithine carboxy-lyase, EC 4.1.1.17) activity in Neurospora crassa. By manipulations of the ornithine supply and by the use of inhibitors of the polyamine pathway, we found that spermidine negatively governs formation of active ornithine decarboxylase and that putrescine promotes inactivation of the enzyme. Direct addition of putrescine or spermidine to cycloheximide-treated cells confirmed the role of putrescine in enzyme inactivation and showed that spermidine had no effect on this process. Increases in ornithine decarboxylase activity caused by blocking spermidine synthesis occurred prior to a significant decrease in the spermidine pool. This is consistent with our previous finding that only 10-20% of the spermidine pool is freely diffusible within N. crassa cells. We presume that only this small fraction of the pool is active in regulation.